From great commission to inclusive education a tangible illustration of missionaries' legacy - Poon-McBrayer, Kim Fong (2019)
This article analysed missionaries' roles in the development of general and special education by examining the relationship between the Great Commission and education and the biblical perspective on disabilities as the foundational links between their work and inclusive education. While missionaries have not been directly involved in the practices of inclusive education today, their work in initiating and formalising special education services has facilitated a more welcoming attitude toward individuals with disabilities, and propelled governments around the globe to make special and inclusive education a public responsibility when socio-political environments demand it. To provide a concrete illustration, this article used Hong Kong as an example by examining missionaries' key involvements and impact in its development of public education from the early colonial era to today's inclusive education. The missionaries' legacy in Hong Kong's inclusive education development lay in their nurturing of Christian educators as supported by a high number of public Christian schools and Christian educators advocated for inclusive education, and in their efforts to formalise special education during the early colonial era (175).
Keywords: Great Commission; Hong Kong; Inclusive Education; missionary roles